Is urine glucose point‐of‐care testing accurate in ruling in or ruling out gestational diabetes mellitus?. Issue 11 (November 2016) - Ford, Brian; Mercado, Michael
Abstract : EVIDENCE‐BASED ANSWER : No, serial urine dipstick glucose testing lacks the sensitivity to rule out gestational diabetes mellitus (GDM). For diagnosing GDM, urine glucose testing performs slightly better, with positive likelihood ratios ranging from 1.5 to 4.6, but is limited by the low prevalence of glucosuria in patients with GDM. Urine glucose testing should not be used for GDM screening during pregnancy (SOR: C, consistent diagnostic cohort studies with disease‐oriented outcomes).